InHand: mobile professional context and location aware tool - Neves, P.A.C.S. (2011)
“Copyright © [2010] IEEE. Reprinted from 16th International Conference on Software, Telecommunications and Computer Networks. SoftCOM 2008. ISBN:978-953-6114-97-9. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”